Development of decellularized meniscus using closed sonication treatment system: as potential scaffolds for orthopedics tissue engineering applications - Mohd Yusof, Fatihah; Sha'ban, Munirah; Noor Azmi, Azran Azhim (Dove Medical Press LTD, 2019)
Purpose: Meniscus is a fibrocartilagenous tissue that cannot effectively heal due to its complex structure and avascular zone present. Thus, tissue engineering and regenerative medicine offer an alternative for the regeneration of meniscus tissues using bioscaffolds as a replacement for the damaged one. The aim of this study is to prepare an ideal meniscus bioscaffold with a minimal adverse effect on extracellular matrix components (ECM) using sonication treatment system.